Factors associated with attendance for pre-pregnancy care and reasons for non-attendance among women with diabetes. (August 2018) - Morrison, Melinda; Hendrieckx, Christel; Nankervis, Alison; Audehm, Ralph; Farrell, Kaye; Houvardas, Effie; Scibilia, Renza; Ross, Glynis P.
Highlights: Women with Type 1 DM were more likely to attend PPC than women with Type 2 DM. Non-attendance was mainly due to lack of awareness of PPC and unexpected pregnancy. Most women indicated willingness to attend PPC if available locally. Strategies are needed to promote awareness and importance of PPC. With increasing rates of Type 2DM, primary care is crucial for promoting PPC. Abstract: Aims: To describe factors associated with the uptake of diabetes-specific pre-pregnancy care (PPC), determine the perceived helpfulness of attending, reasons for non-attendance and intention to seek PPC in the future. Methods: A cross-sectional 66-item survey was administered to Australian women with type 1 or type 2 diabetes mellitus (DM) aged 18–50 years. Results: Of 429 eligible women, 54% reported having attended PPC. In multivariable logistic regression analysis, having Type 1 DM [adjusted OR 1.89, 95% CI (1.07, 3.33)], being married or in a defacto relationship [OR 2.43 (95% CI 1.27, 4.65)], tertiary educated [OR 1.91 (95% CI 1.27, 2.88)] or employed [OR 1.80 (95% CI 1.14, 2.82)] were associated with being more likely to attend PPC. Sixty eight percent (68%) rated attending PPC as helpful. A lack of awareness about the availability of PPC (48%) and unplanned pregnancy (47%) were the main reasons for non-attendance. Of women with future pregnancy plans, 43% were aware of local services offering PPC and 84% indicated they would attend PPC if available. Conclusion: Australian women who attend PPC differ by type of diabetes and socioeconomic characteristics. Initiatives are needed to address this disparity and encourageall women with diabetes to plan and prepare for pregnancy. Reasons reported for non-attendance suggest that strategies to increase awareness about the availability of diabetes-specific PPC and the risks of unplanned pregnancy are warranted.